Molding film for in-mold transfer, and method for manufacturing molded article

CN119365341BActive Publication Date: 2026-10-23TORAY INDUSTRIES INC
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380047153.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2022-06-16
Filing Date
2023-05-16
Publication Date
2026-10-23
Estimated Expiration
2043-05-16

AI Technical Summary

Benefits of technology

[0026]根据本发明,可以提供成型性和成型加工后的导电性、电磁波屏蔽性优异、使生产率良好的模内转印用成型膜、成型品的制造方法。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005187381780000181
    Figure BDA0005187381780000181
  • Figure BDA0005187381780000191
    Figure BDA0005187381780000191
Patent Text Reader

Abstract

Provided is a molding film for in-mold transfer, which is excellent in moldability and electric conductivity after molding processing, electromagnetic wave shielding property, and productivity, and a method for manufacturing a molded product. A molding film for in-mold transfer, which has, in order, a base film, a release layer, and a conductive layer, the conductive layer containing 60 mass% or more and 91 mass% or less of particles in 100 mass% of the conductive layer, the conductive layer containing 9 mass% or more and 40 mass% or less of a resin, the resin having a weight average molecular weight of 5,000 or more and less than 10,000, the particles containing one or more selected from carbon, silver, gold, copper, nickel, chromium, palladium, indium, aluminum, zinc, and platinum.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a molding film for in-mold transfer and a method for manufacturing molding articles. Background Technology

[0002] In recent years, with the expansion of the IoT society, the requirements for electromagnetic wave shielding performance have become increasingly stringent in fields such as mobile phones, electronic products, and automotive parts. When resin is used for the frame, methods such as plating and conductive coating are known for processing the molded product. However, these conventional methods require environmental countermeasures such as drainage treatment and solvent post-treatment, and various attempts have been made to improve this.

[0003] For example, Patent Document 1 discloses a technique for in-mold transfer molding of a molding film having a conductive layer comprising resin and conductive particles. Patent Document 2 discloses a technique for in-mold transfer molding of a molding film having a conductive layer composed of metal and a conductive polymer resin.

[0004] Existing technical documents

[0005] Patent documents

[0006] Patent Document 1: Japanese Patent Application Publication No. 2021-192960

[0007] Patent Document 2: Japanese Patent Application Publication No. 2006-297642 Summary of the Invention

[0008] The problem that the invention aims to solve

[0009] However, in the technology described in Patent Document 1, in-plane deviations occur in the conductive layer when in-mold transfer molding is performed, thus causing problems with conductivity and electromagnetic wave shielding. On the other hand, in the technology described in Patent Document 2, cracks and breaks occur in the conductive layer when the molded article has a complex shape, thus causing problems with formability.

[0010] The objective of this invention is to improve upon the problems of the prior art by providing an in-mold transfer molding film with excellent formability, conductivity after molding, electromagnetic wave shielding, and high productivity, as well as a method for manufacturing the molded article.

[0011] Solution for solving the problem

[0012] In order to solve the above-mentioned problems, the present invention has conducted in-depth research and found that the problem is solved by the following method, thereby completing the present invention. Specifically, a preferred embodiment of the method for manufacturing the in-mold transfer molding film and the molded article of the present invention adopts the following configuration.

[0013] (1) An in-mold transfer molding film comprising, in sequence, a substrate film, a release layer, and a conductive layer, wherein the conductive layer contains 60% or more and 91% or less particles in 100% by mass of the conductive layer, the conductive layer contains 9% or more and 40% or less resin, the resin having a weight average molecular weight of 5,000 or more and less than 10,000, and the particles comprising one or more of carbon, silver, gold, copper, nickel, chromium, palladium, indium, aluminum, zinc and platinum with zero valence.

[0014] (2) The molding film for in-mold transfer according to (1), wherein the thickness of the conductive layer is 5 μm or more and 15 μm or less.

[0015] (3) The in-mold transfer molding film according to (1) or (2), wherein, for the conductive layer, when heated from 20°C to 250°C at 20°C / min in a nitrogen atmosphere using a differential scanning calorimeter, the glass transition temperature is observed in the range of 40°C or higher and 100°C or lower.

[0016] (4) The in-mold transfer molding film according to any one of (1) to (3) comprises, in sequence, the substrate film, the release layer, the conductive layer, and the adhesive layer.

[0017] (5) The molding film for in-mold transfer according to any one of (1) to (4), wherein the release layer is mainly composed of silicone resin.

[0018] (6) The molding film for in-mold transfer according to (5), wherein the release layer is mainly composed of alkyd modified silicone resin.

[0019] (7) The molding film for in-mold transfer according to any one of (1) to (6), wherein the resin is a polyester resin.

[0020] (8) The molding film for in-mold transfer according to (7), wherein the acid value of the polyester resin is 5 mg KOH / g or more and 20 mg KOH / g or less.

[0021] (9) The molding film for in-mold transfer according to any one of (1) to (8), wherein the particles are a first particle with an aspect ratio of 1 or more and less than 2 and a second particle with an aspect ratio of 2 or more.

[0022] (10) The molding film for in-mold transfer according to any one of (1) to (9), wherein the electromagnetic wave shielding effect of the molding film for in-mold transfer when measured by the KEC method (electric field) using electromagnetic waves with a frequency of 300 MHz is 40 dB or more.

[0023] (11) The in-mold transfer molding film according to any one of (1) to (10), wherein the substrate film is a polyethylene terephthalate film.

[0024] (12) A method for manufacturing a molded article, comprising the step of placing an in-mold transfer molding film as described in any one of (1) to (11) in a mold, and then injecting a molding resin and / or a molding resin precursor.

[0025] The effects of the invention

[0026] According to the present invention, there is a method for manufacturing an in-mold transfer molding film and a molded article that provides excellent formability, conductivity after molding, electromagnetic wave shielding, and high productivity. Detailed Implementation

[0027] A preferred embodiment of the in-mold transfer molding film of the present invention is an in-mold transfer molding film comprising, in sequence, a substrate film, a release layer, and a conductive layer, wherein the conductive layer contains 60% to 91% by mass particles in 100% by mass, the conductive layer contains 9% to 40% by mass resin, the resin has a weight-average molecular weight of 5000 or more and less than 10000, and the particles comprise one or more selected from carbon, silver, gold, copper, nickel, chromium, palladium, indium, aluminum, zinc, and platinum with zero valence. The in-mold transfer molding film of the present invention will be specifically described below.

[0028] [Conductive layer]

[0029] In this invention, a preferred embodiment of the conductive layer is that 100% by mass of the conductive layer contains 60% by mass and 91% by mass of particles, and the conductive layer contains 9% by mass and 40% by mass of resin. By employing this method, even after the conductive layer is heated during the molding process, no micro-cracks will be generated, resulting in excellent moldability.

[0030] Furthermore, by making the weight-average molecular weight of the resin 5,000 or more and less than 10,000, and by including the aforementioned particles one or more selected from carbon, silver, gold, copper, nickel, chromium, palladium, indium, aluminum, zinc and platinum with zero valence, even after heating the conductive layer through molding, the in-plane deviation of the conductive layer can be reduced, thus enabling excellent conductivity and electromagnetic wave shielding after molding.

[0031] From the above perspective, by including 60% or more particles, the particle composition ratio in the conductive layer can be increased, thereby improving the conductivity and electromagnetic wave shielding properties after molding. From the same perspective, it is more preferable to include 65% or more particles, and even more preferable to include 70% or more particles.

[0032] Furthermore, by containing 91% or less of particles, the resin content in the conductive layer can be increased, thereby improving moldability. From the same point of view, it is more preferable to contain 87% or less of particles, and even more preferable to contain 85% or less of particles.

[0033] Based on the above viewpoint, for the particles in this invention, when all components constituting the conductive layer are set to 100% by mass, it is more preferable to contain particles of 65% or more and 87% or less by mass, and even more preferably particles of 70% or more and 85% or less by mass.

[0034] From the viewpoint of achieving good conductivity and electromagnetic wave shielding after molding, the particles of the present invention preferably contain one or more selected from carbon, silver, gold, copper, nickel, chromium, palladium, indium, aluminum, zinc, and platinum (all with zero valence). From the viewpoint that lower resistivity leads to better conductivity and electromagnetic wave shielding, it is more preferable to contain one or more selected from gold, silver, silver-plated copper powder, and alloys of silver and copper. "Zero valence" refers not only to carbon but also to all metallic elements.

[0035] In the particles exemplified above, whether the particles contain zero-valent metal elements can be determined by energy-dispersive X-ray spectroscopy mapping analysis (hereinafter referred to as EDX mapping analysis) on the cross-section obtained by cutting the molded film for in-mold transfer, based on whether zero-valent metal elements are detected in the particle portion. EDX mapping analysis can be performed, for example, using a scanning electron microscope (FEI Corporation, XL30 SFEG) equipped with an energy-dispersive X-ray spectrometer (EDAX Corporation, NEW XL30132-2.5) at an accelerating voltage of 20 kV and a magnification of 20,000x. Alternatively, the cutting device for the molded film for in-mold transfer can be a "Cross Section Polisher" (registered trademark) SM-09010 (JEOL Corporation), etc., where the sample is obtained by treating it with argon gas for 10 hours at an accelerating voltage of 4 kV and a current of 70 μA. Regarding carbon particles, these refer to particles that have undergone qualitative analysis by performing micro-Raman mapping analysis on the cross-section obtained using the same method as described above. Micro-Raman mapping analysis can be performed, for example, using a micro-laser Raman spectroscopy apparatus (manufactured by Horiba Manufacturing Co., Ltd., "LabRAM" (registered trademark) HR Evolution).

[0036] Since the overlap between particles in the conductive layer after molding can be maintained by making the particles contain a first particle with an aspect ratio of 1 or more and less than 2 and a second particle with an aspect ratio of 2 or more, the electromagnetic wave shielding after molding can be further improved.

[0037] Based on the same viewpoint as above, when all components constituting the conductive layer are set to 100% by mass, it is preferable that the content of the first particle is 20% or more and 70% or less by mass, and the content of the second particle is 10% or more and 60% or less by mass.

[0038] It should be noted that in this invention, "particle" refers to a primary particle. Therefore, the first particle refers to a primary particle with an aspect ratio of 1 or more and less than 2, and the second particle refers to a primary particle with an aspect ratio of 2 or more. As a method for calculating the average particle size of primary particles, a scattering particle size distribution measuring device (manufactured by Horiba Manufacturing Co., Ltd., LA-960V2) can be used, for example.

[0039] The aspect ratio of the particles referred to here can be calculated as the ratio of the average major axis to the average minor axis of the particles. One method for calculating this ratio is, for example, to observe the cross-section of the conductive layer obtained by cutting the in-mold transfer molding film using a scanning electron microscope (FEI Corporation, XL30 SFEG) at an accelerating voltage of 20 kV and a magnification of 100,000. Fifty particles are extracted from the obtained image, and each particle is approximated as an ellipse. The average of the longest lengths is used as the average major axis, and the shortest length is used as the average minor axis to calculate the aspect ratio. Alternatively, a manual rotating microscope microtome (Leica Microsystems Corporation, "HistoCore BIOCUT" (registered trademark)) can be used to obtain the sample.

[0040] Furthermore, by containing 40% or less of resin, the component ratio of particles to all components constituting the conductive layer can be increased, thereby improving the conductivity and electromagnetic wave shielding properties after molding. From the same point of view, it is more preferable to contain 25% or less of resin, and even more preferable to contain 20% or more of resin.

[0041] Furthermore, by containing 9% or more of resin, the dispersion of particles in the conductive layer and the overall moldability and flexibility of the conductive layer can be improved, thus enhancing moldability. From the same point of view, it is more preferable to contain 10% or more of resin, and even more preferable to contain 13% or more of resin.

[0042] Based on the above viewpoint, for the resin of the present invention, it is more preferable to contain 10% or more and 25% or less of resin in 100% by mass of conductive layer, and even more preferable to contain 13% or more and 20% or less of resin.

[0043] From the perspective of improving moldability, conductivity after molding, and electromagnetic wave shielding, the weight-average molecular weight of the resin is preferably 5000 or more and less than 10000.

[0044] By increasing the weight-average molecular weight of the resin to 5000 or higher, the resin viscosity increases, stabilizing the flowability of the conductive layer during the molding process. This reduces the in-plane deviation of the conductive layer, resulting in excellent conductivity and electromagnetic wave shielding. From the same perspective, it is more preferable to increase the weight-average molecular weight of the resin to 7500 or higher.

[0045] Furthermore, by making the weight-average molecular weight of the resin less than 10,000, the resin's flowability is improved during the molding process, resulting in excellent moldability. From the same point of view, it is more preferable to make the weight-average molecular weight of the resin 9,000 or less, and even more preferable to make it 8,500 or less.

[0046] Based on the above viewpoints, the weight-average molecular weight of the resin of the present invention is more preferably 7,500 or more and 9,000 or less.

[0047] The weight-average molecular weight of the resin can be calculated using the styrene-converted molecular weight determined by GPC (gel permeation chromatography). The method for determining the weight-average molecular weight of the resin using GPC is as follows.

[0048] The apparatus used for analysis consisted of two separation columns (PLgel 5μm MiniMIX-D, Agilent Technologies, Inc.) connected in series on a high-speed GPC unit (HLC-8220, Tosoh Corporation). Polystyrene standards (weight-average molecular weight: 5000, 10000, 30000) were added to chloroform and stirred at 20°C for 10 minutes. The standard sample solution, filtered through a 0.45μm membrane filter, was then measured to create a standard curve. Next, 5 mg of the conductive layer was added to 2 mL of chloroform and stirred at 20°C for 10 minutes. The sample, filtered through a 0.45μm membrane filter, was then used for analysis to calculate the weight-average molecular weight of the resin. Here, the flow rate in the separation column was set to 0.35 mL / min, the column temperature to 40°C, and a differential refractometer (RI detector, Tosoh Corporation) was used as the detector. It should be noted that by separating and weighing each peak, the content of each peak related to the resin can be determined.

[0049] From the viewpoint of satisfying formability and conductivity and electromagnetic wave shielding after molding, the conductive layer of the present invention preferably has a glass transition temperature that is observed in the range of 40°C to 100°C when heated from 20°C to 250°C at a rate of 20°C / min in a nitrogen atmosphere using a differential scanning calorimeter.

[0050] By observing the glass transition temperature of the conductive layer below 100°C, sufficient flexibility can be exhibited during the molding process, thus resulting in excellent formability. From the same point of view, it is more preferable to observe the glass transition temperature of the conductive layer below 80°C.

[0051] Furthermore, by observing the glass transition temperature of the conductive layer above 40°C, the fluidity of the conductive layer is stabilized during the molding process, thereby reducing in-plane deviation of the conductive layer. This results in excellent conductivity and electromagnetic wave shielding after molding. From this perspective, it is more preferable to observe the glass transition temperature of the conductive layer above 60°C.

[0052] Based on these viewpoints, in this invention, it is more preferable to observe the glass transition temperature of the conductive layer at a temperature above 60°C and below 80°C.

[0053] The glass transition temperature of the conductive layer can be determined using a known differential scanning calorimeter. Specifically, the glass transition temperature of the conductive layer is determined and analyzed using a differential scanning calorimeter (Seiko Instruments Co., Ltd., RDC220) according to the following method based on JIS K7121 (2012).

[0054] Only the conductive layer was removed from the in-mold transfer molding film. The resulting conductive layer was heated at 100°C for 4 hours under a nitrogen atmosphere, then cooled to 25°C to prepare a 5mg sample. The specific heat change was measured based on the transition from the glassy to the rubbery state of the sample when heated from 20°C to 250°C at a rate of 20°C / min under a nitrogen atmosphere. The glass transition temperature was determined as the midpoint of the intersection of straight lines equidistant from each baseline along the longitudinal axis (representing the heat flow) with the curve of the step-like transition portion of the glass transition.

[0055] From the viewpoint of improving moldability and conductivity, as well as electromagnetic wave shielding, the resin in the conductive layer is preferably a polyester resin as the main component. "The resin in the conductive layer is preferably a polyester resin as the main component" means that when the content of the resin in the conductive layer is set to 100% by mass, it contains 50% by mass or more of polyester resin. By adopting this method, the softness and particle dispersibility of the resin can be improved, thus resulting in excellent moldability, conductivity, and electromagnetic wave shielding. From the same viewpoint, when the content of the resin is set to 100% by mass, it is more preferable to contain 80% by mass or more of polyester resin. Furthermore, from the above viewpoint, the resin contained in the conductive layer is further preferably a polyester resin. Also, from the same viewpoint, it is preferable that the aforementioned polyester resin is a saturated polyester resin, and from the viewpoint of durability, it is further preferable that the aforementioned polyester resin is a thermoplastic saturated polyester resin.

[0056] For the aforementioned polyester resin, from the viewpoint of improving moldability, conductivity after molding, and electromagnetic wave shielding, the acid value of the polyester resin is preferably above 5 mg KOH / g and below 20 mg KOH / g.

[0057] By increasing the acid value of the polyester resin to 5 mg KOH / g or higher, the adhesion between the resin and the release layer is improved, thereby reducing the in-plane deviation of the conductive layer after the molding process. This results in excellent conductivity and electromagnetic wave shielding. From the same point of view, it is more preferable to increase the acid value of the polyester resin to 7 mg KOH / g or higher.

[0058] Furthermore, by setting the acid value of the polyester resin to 20 mg KOH / g or less, the dispersibility of the particles and the polyester resin is improved, thereby enabling excellent moldability. From the same point of view, it is more preferable to set the acid value of the polyester resin to 15 mg KOH / g or less.

[0059] Based on the above viewpoint, it is preferable that the acid value of the aforementioned polyester resin is 5 mg KOH / g or higher and 20 mg KOH / g or lower, and that the weight-average molecular weight is 7500 or higher and 9000 or lower.

[0060] Qualitative / quantitative analysis methods for polyester resins can be exemplified by the following method: only the conductive layer is removed from the in-mold transfer molding film, the obtained conductive layer sample is freeze-dried, and the recovered dried solids are qualitatively / quantitatively analyzed by gas chromatography-mass spectrometry (P&T-GC / MS) equipped with a purge trap sampler (heated desorption device).

[0061] The acid value of polyester resin can be determined by titration according to JIS K 5601-2-1 (1999). Specifically, the sample can be dissolved in a mixed solvent of toluene / ethanol in a volume ratio of 2 / 1, and titrated with potassium hydroxide solution using phenolphthalein as an indicator. The acid value can then be determined by titration according to JIS K 5601-2-1 (1999) using the following formula.

[0062] Acid value (mgKOH / g) = 56.1 × V × C / m

[0063] V: titration volume (ml), C: concentration of titrant (mol / L), m: mass of solid components of the sample (g).

[0064] From the viewpoint of satisfying conductivity and electromagnetic wave shielding after molding, the thickness of the conductive layer of the present invention is preferably 5 μm or more and 15 μm or less. By making the thickness of the conductive layer 15 μm or less, the conductive layer can be stably heated during the molding process, thereby reducing the in-plane deviation of the conductive layer, and thus enabling excellent conductivity and electromagnetic wave shielding after molding. From the same viewpoint, the thickness of the conductive layer is more preferably 12 μm or less. In addition, by making the thickness of the conductive layer 5 μm or more, the particle content in the conductive layer increases, the resistivity of the conductive layer decreases, thereby fully utilizing conductivity and electromagnetic wave shielding, and enabling excellent conductivity and electromagnetic wave shielding after molding. From the same viewpoint, the thickness of the conductive layer is more preferably 7 μm or more.

[0065] Electromagnetic wave shielding

[0066] By employing the above-described manner, the molding film for in-mold transfer of the present invention can achieve an electromagnetic wave shielding effect of 40 dB or more when measuring electromagnetic waves using the KEC method (electric field) at a frequency of 300 MHz.

[0067] The KEC method is a measurement method specified by the Kansai Electronics Industry Promotion Center. It evaluates the shielding effect of near-field electromagnetic waves by dividing it into electric and magnetic fields. The measurement using this method can be performed by receiving electromagnetic waves transmitted from a transmitting antenna (transmitting fixture) via an electromagnetic wave shielding film (test sample) and a receiving antenna (receiving fixture). In the KEC method, the electromagnetic waves that pass through the electromagnetic wave shielding film in the receiving antenna are measured. That is, by measuring how much the transmitted electromagnetic wave (signal) is attenuated at the receiving antenna side by the electromagnetic wave shielding film, the electromagnetic wave shielding performance that blocks (shields) the electromagnetic waves is determined by summing the reflected component of the reflected electromagnetic wave and the absorbed component of the absorbed electromagnetic wave.

[0068] The molding film for in-mold transfer of the present invention preferably has an electromagnetic wave shielding effect of 40dB or more when measured by the KEC method (electric field) for electromagnetic waves with a frequency of 300MHz.

[0069] [Mold Release Layer]

[0070] The release layer of the present invention is not particularly limited as long as it is used to peel the conductive layer and the substrate film. From the viewpoint of maximizing productivity, it is preferable to use silicone resin as the main component. By making silicone resin the main component of the release layer, and more preferably making the silicone resin content in the release layer 80% by mass or more, the adhesion between the substrate film and the conductive layer can be controlled. Therefore, both the processability of the conductive layer and the peelability of the substrate film during the molding process can be taken into account.

[0071] From the viewpoint of controlling the adhesion to the conductive layer, modified silicone resins produced by graft polymerization with organic resins, such as polyester modified silicone resins, acrylic modified silicone resins, polyurethane modified silicone resins, epoxy modified silicone resins, and alkyd modified silicone resins, are more preferred. From the viewpoint of being able to control the adhesion to polyester resins, alkyd modified silicone resins are even more preferred.

[0072] [Substrate Film]

[0073] From the viewpoint of good dimensional stability, durability, and improved productivity, the substrate film of the present invention is preferably a plastic film formed of polyester, such as polyethylene terephthalate, polyethylene 2,6-naphthalenedicarboxylate, polyethylene α,β-bis(2-chlorophenoxy)ethane 4,4'-dicarboxylate, and polyethylene terephthalate. From the viewpoint of excellent processability in the lamination and molding process of the release layer and conductive layer, a film formed of polyethylene terephthalate is particularly preferred, and from the same viewpoint, biaxially stretched polyethylene terephthalate is most preferred.

[0074] [Mold transfer molding film]

[0075] The in-mold transfer molding film of the present invention has excellent formability and conductivity and electromagnetic wave shielding properties after molding. Therefore, it can easily be used to apply conductive and electromagnetic wave shielding layers to molded articles with curved surfaces, concave and convex ribs, hinges, protrusions, and hollow shapes. That is, because the in-plane deviation of conductivity and electromagnetic wave shielding is small, it can be more suitable as an in-mold transfer molding film for imparting conductivity and electromagnetic wave shielding properties to molded articles. In particular, because the in-plane deviation of electromagnetic wave shielding is small, it can be further suitable as an in-mold transfer molding film for imparting electromagnetic wave shielding properties to molded articles.

[0076] Based on the above viewpoints, the application is not limited as long as the effect of the present invention is not impaired. For example, it can be appropriately used to impart electromagnetic shielding properties to personal computers, monitors, OA equipment, mobile phones, portable information terminals, optical equipment, audio equipment, air conditioners, lighting equipment, entertainment equipment, toys, other household appliances, electronic equipment, semiconductor components, electrical components and internal parts of automobiles, electrical components and internal parts of aircraft, electrical components and internal parts of two-wheeled vehicles, etc.

[0077] From the viewpoint of bonding a conductive layer to a resin and / or a resin precursor, the molding film for in-mold transfer of the present invention further preferably comprises a substrate film, a release layer, a conductive layer, and an adhesive layer in sequence, with the adhesive layer being the outermost layer.

[0078] In the in-mold transfer molding film of the present invention, the resin used in the adhesive layer, that is, the resin contained in the adhesive layer, can be a heat-sensitive resin or a pressure-sensitive resin, and the raw materials of the adhesive layer can be appropriately selected according to the material of the resin and / or resin precursor.

[0079] The resin contained in the adhesive layer is preferably an acrylic resin, polyester resin, polyphenylene ether / polystyrene resin, polycarbonate resin, polystyrene resin, styrene copolymer resin, polyamide resin, chlorinated polyolefin resin, chlorinated vinyl acetate copolymer resin, cyclized rubber, coumarone-indene resin, etc., used alone or in combination.

[0080] [Manufacturing method of molding film for in-mold transfer]

[0081] The manufacturing method of in-mold transfer molding film can be exemplified by the following examples, including materials, usage amounts, processing contents, and processing steps.

[0082] The in-mold transfer molding film of the present invention can be manufactured, for example, by sequentially coating a release layer coating material composition and a conductive layer coating material composition on one side of a substrate film and then performing heat treatment.

[0083] The coating material composition for the release layer in this invention can be obtained by mixing an organosilicon resin and an organic solvent. Regarding the organic solvent used in the coating material composition for the release layer in this invention, when the total components constituting the resin mixture of the organosilicon resin and the organic solvent are set to 100% by mass, from the viewpoint of achieving good coatability to the substrate film, it is preferable that the organic solvent is 50% by mass or more and 99% by mass or less. From the viewpoint of improving the coatability of the coating material composition for the release layer, examples of organic solvents include ethyl methyl ketone, methyl isobutyl ketone, butyl acetate, ethyl acetate, methanol, isopropanol, cyclohexanone, toluene, xylene, etc. Furthermore, in the coating material composition, as long as it does not impair the effects of this invention, from the viewpoint of preventing adhesion when wound into a film roll and improving the coatability to the substrate film, inorganic particles, organic particles, leveling agents, etc., can be incorporated.

[0084] The coating material composition for the conductive layer in this invention can be obtained by mixing a resin mixture of particles, resin, and a mixing organic solvent, and then mixing with a diluting organic solvent. Regarding the particles used in the resin mixture of this invention, when the total components comprising particles and resin are set to 100% by mass, it is preferable that the particles comprise 60% by mass or more and 91% by mass or less. Furthermore, regarding the resin used in the resin mixture of this invention, when the total components comprising particles and resin are set to 100% by mass, it is preferable that it contains 9% by mass or more and 40% by mass or less of resin. Regarding the mixing organic solvent used in the resin mixture of the conductive layer of this invention, when the total components constituting the resin mixture of particles, resin, and mixing organic solvent are set to 100% by mass, from the viewpoint of ensuring good mixing and dispersion of particles and resin, it is preferable that the mixing organic solvent comprises 5% by mass or more and 50% by mass or less. From the viewpoint of suppressing the volatilization of the organic solvent used for mixing when mixing particles and resin, and suppressing the thickening of the resin mixture, it is further preferred that, for example, N,N-dimethylacetamide, N,N-dimethylformamide, N-methyl-2-pyrrolidone, dimethylimidazolinone, dimethyl sulfoxide, γ-butyrolactone, ethyl lactate, 1-methoxy-2-propanol, 1-ethoxy-2-propanol, ethylene glycol monopropyl ether, diacetone alcohol, tetrahydrofurfuryl alcohol, propylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether acetate (hereinafter referred to as "DMEA"), diethylene glycol monobutyl ether, diethylene glycol, and 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate be used alone or in combination.

[0085] Regarding the dilution organic solvent in this invention, when the total components of the resin composition consisting of the resin mixture and the dilution organic solvent are set to 100% by mass, from the viewpoint of balancing the coatability when the conductive layer is applied to the release layer and the thickness of the conductive layer, it is preferable that the dilution organic solvent is 10% by mass or more and 80% by mass or less. Examples of organic solvents for mixing include ethyl methyl ketone, methyl isobutyl ketone, butyl acetate, ethyl acetate, methanol, isopropanol, cyclohexanone, toluene, xylene, etc.

[0086] The method for mixing the particles, polyurethane resin and mixing organic solvent in the resin mixture of the present invention can be, for example, a known mixing and dispersion method such as a three-roll mill, ultrasonic disperser, sand mill, clay dry pulverizer, coarse crusher, ultrafine pulverizer, ball mill, impeller, disperser, KD mill, colloid mill, negative resistance tube, planetary mill and pressure kneader.

[0087] The method of mixing the resin mixture and the diluent organic solvent in the aforementioned resin composition can be any known mixing and dispersion method such as magnetic stirrer, homogenizer, ultrasonic irradiation, vibration dispersion, and manual mixing and dispersion.

[0088] As a method for sequentially coating a release layer and a conductive layer onto one side of a substrate film, the release layer and conductive layer are preferably formed by coating using methods such as comma coating, applicator coating, dip coating, roller coating, wire rod coating, reverse coating, coincidence coating, gravure printing coating, or die coating (as described in U.S. Patent No. 2,681,294). From a processability point of view, applicator coating, comma coating, reverse coating, and die coating are further preferred.

[0089] The molding film for in-mold transfer of the present invention is preferred for use as an in-mold transfer film because of its excellent formability, conductivity after molding, electromagnetic wave shielding, and good productivity.

[0090] That is, a preferred method for manufacturing molded articles includes the steps of placing an in-mold transfer molding film in a mold and then injecting resin and / or resin precursor.

[0091] This process can be constructed using known injection molding machines and film feeding mechanisms. For example, the S-2000 type (manufactured by Fanuc Co., Ltd.) can be used as the injection molding machine, and the roller foil stamping machine (Horagin Foil Powder Co., Ltd.) can be used as the film feeding machine.

[0092] [Manufacturing method for molded parts: In-mold transfer injection molding]

[0093] The method for manufacturing the molded article of the present invention can preferably employ a process that includes placing an in-mold transfer molding film in a mold and then injecting molding resin and / or molding resin precursor.

[0094] Specifically, for example, a preferred method for obtaining a molded article may be adopted in the following order: passing the in-mold transfer molding film of the present invention through the mold of an injection molding machine, arranging the conductive layer side of the aforementioned molding film toward the cavity of the in-mold transfer injection molding mold, and performing injection molding thereon as a molding resin and / or molding resin precursor, thereby transferring the conductive layer of the aforementioned molding film onto the surface of the injection resin, and after cooling the injection resin, opening the injection molding mold and peeling off the substrate film of the aforementioned molding film.

[0095] The molding resin and / or molding resin precursor of the present invention are preferably thermoplastic resins or elastomers, and more preferably resins such as polybutylene terephthalate (PBT), polyphenylene sulfide, polycarbonate, polyacetal, polyethylene terephthalate, polyphenylene ether, polyacrylate, polyamide, polypropylene, acrylic resins, polystyrene, polyacrylonitrile-styrene, polyacrylonitrile-butadiene-styrene (ABS), and epoxy resin, used alone or in combination. In addition, glass fibers, inorganic fillers, etc., may be appropriately added to the resin as reinforcing materials.

[0096] Example

[0097] The following examples illustrate the invention in detail, but the invention is not limited to these examples.

[0098] It should be noted that the measurement and evaluation methods in this embodiment are as follows.

[0099] (1) Thickness of conductive layer and adhesive layer

[0100] The thickness (μm) of the conductive layer and the adhesive layer was determined as follows: using a manual rotating microscope microtome (manufactured by Leica Microsystems Co., Ltd., "HistoCore BIOCUT" (registered trademark) R), the in-mold transfer molding film was cut in a direction perpendicular to the thickness to obtain a cross-section of the in-mold transfer molding film. The cross-section of the conductive layer was observed using a scanning electron microscope (manufactured by FEI Co., Ltd., XL30 SFEG) at an accelerating voltage of 20kV and an observation magnification of 100,000x. Based on the cross-sectional photograph, five arbitrary points were measured, and the average value of the obtained values ​​was calculated.

[0101] (2) Aspect ratio of the particles

[0102] In the method of (1), 50 particles are extracted from the obtained scanning electron microscope image. Each particle is approximated as an ellipse, with the maximum length as the major axis and the minimum length as the minor axis, and the aspect ratio of each particle is calculated. Then, a histogram is created using the obtained aspect ratios at a scale of 0.1, and the value of the peak is used as the aspect ratio of the second particle. In the case of two peaks, the peak with the smaller value is used as the aspect ratio of the first particle, and the peak with the larger value is used as the aspect ratio of the second particle.

[0103] (3) Glass transition temperature of the conductive layer

[0104] The measurements and analyses were performed using a differential scanning calorimeter (Seiko Instruments Co., Ltd., RDC220) according to the following method in JIS K7121 (2012).

[0105] A 5 mg sample of conductive layer or thermoplastic resin was used. For evaluation of the conductive layer or thermoplastic resin, the conductive layer or thermoplastic resin was heated at 100°C for 4 hours under a nitrogen atmosphere, then cooled to 25°C to prepare a 5 mg sample. The specific heat change was recorded based on the transition from the glassy state to the rubbery state when the sample was heated from 20°C to 250°C at a rate of 20°C / min under a nitrogen atmosphere. The glass transition temperature was determined as the midpoint of the intersection of the straight lines extending from each baseline along the longitudinal axis (representing the heat flow) with the curve of the step-like transition portion of the glass transition.

[0106] (4) Weight-average molecular weight of resin

[0107] The molecular weight analysis of the thermoplastic resin contained in the conductive layer was performed using the following method, and the weight-average molecular weight was evaluated based on the detected peak area.

[0108] <Molecular Weight Analysis Methods>

[0109] The apparatus used for analysis consisted of two separation columns (PLgel 5μm MiniMIX-D, Agilent Technologies, Inc.) connected in series on a high-speed GPC device (HLC-8220, Tosoh Corporation). Polystyrene standards (weight-average molecular weight: 5000, 10000, 30000) were added to chloroform and stirred at 20°C for 10 minutes. The standard sample solution, filtered through a 0.45μm membrane filter, was then analyzed to create a standard curve. Next, 5 mg of the conductive layer was added to 2 mL of chloroform and stirred at 20°C for 10 minutes. The sample, filtered through a 0.45μm membrane filter, was then used for analysis. Here, the flow rate in the separation column was set to 0.35 mL / min, the column temperature to 40°C, and a differential refractometer (RI detector, Tosoh Corporation) was used as the detector.

[0110] (5) Electromagnetic wave shielding effect of molding film for in-mold transfer

[0111] The in-mold transfer molding film was cut into 120mm × 120mm pieces, and the KEC method (electric field) was used for measurement. The electromagnetic wave shielding effect (dB) at a frequency of 300MHz was calculated using a spectrum analyzer. The results were taken as the electromagnetic wave shielding effect of the in-mold transfer molding film. The higher the electromagnetic wave shielding effect, the better the electromagnetic wave shielding performance.

[0112] (6) Electromagnetic wave shielding effect of in-mold transfer molding film when stretched by 1.1 times in length × 1.1 times in width

[0113] The in-mold transfer molding film was cut into 120mm × 120mm pieces. Using a Brueckner LAB-STRETCHING KARO 5.0, the film was simultaneously subjected to biaxial stretching at a ratio of 1.1 times longitudinally × 1.1 times transversely to create samples. The KEC (electric field) method was used for measurement, and the electromagnetic wave shielding effect (dB) at a frequency of 1 GHz was measured using a spectrum analyzer. The results were taken as the electromagnetic wave shielding effect at 1 GHz. A higher electromagnetic wave shielding effect indicates better electromagnetic wave shielding performance.

[0114] (7) Processing adaptability of molding process

[0115] After the roll of in-mold transfer molding film is installed in the film feeder, i.e., the roller foil stamping machine (Horagin Foil Powder Co., Ltd.) of the injection molding machine ROBO SHOT S20000i 150A (manufactured by Fanuc Co., Ltd.), it passes through the injection molding mold, and the conductive layer side of the in-mold transfer molding film is positioned towards the cavity of the in-mold transfer injection molding mold (a tile-shaped molded product with a width of 30mm, a length of 300mm, a height of 10mm, and a processing temperature of 80°C). A molded article is obtained in the following order: Polybutylene terephthalate resin (Toray Industries, Inc. "TRECON" (registered trademark) 1101G) is used as molding resin A, and polyacrylonitrile-butadiene-styrene resin (Toray Industries, Inc. "TOYOLAC" (registered trademark) 100) is used as molding resin B. These molding resins are then used as injection molding resins to transfer a conductive layer of the in-mold transfer molding film onto the surface of the injection molding resins. After cooling, the injection molding mold is opened, and the substrate film of the in-mold transfer molding film is peeled off. The processing suitability of the molding process is evaluated according to the following criteria based on the state of the conductive layer when the injection molding mold is opened.

[0116] It should be noted that when using polybutylene terephthalate resin (TRECON (registered trademark) 1101G manufactured by Toray Industries, Inc.) as molding resin A, the melt temperature of the injection resin is 260°C, the injection speed is 8 mm / s, and the cooling time is 25 seconds. When using polyacrylonitrile-butadiene-styrene resin (TOYOLAC (registered trademark) 100 manufactured by Toray Industries, Inc.) as molding resin B, the melt temperature of the injection resin is 230°C, the injection speed is 8 mm / s, and the cooling time is 25 seconds.

[0117] A: There are no abnormalities between the molded part and the substrate film. A conductive layer has been transferred onto the surface of the molded part.

[0118] B: After opening the injection molding mold, the conductive layer transferred to the surface of the molded product is uneven, or the portion of the molded product surface where the conductive layer should be transferred is less than 20% without the conductive layer.

[0119] C: More than 20% of the surface of the molded part that should have a conductive layer transferred has not had the conductive layer transferred.

[0120] (8) Formability of in-mold transfer molding film

[0121] In the method of (7), the in-mold transfer molding film is visually observed before the injection molding mold is opened and the substrate film of the in-mold transfer molding film is peeled off, and the evaluation is carried out according to the following criteria.

[0122] A: The conductive layer and the substrate film conform to the molded product. This is a good result.

[0123] B: The conductive layer and substrate film conform to the molded product, but a portion of the conductive layer or substrate film develops cracks. This is not a practical problem.

[0124] C: The conductive layer and substrate film do not conform to the molded product. Or, cracks appear in the conductive layer or substrate film. The product is unusable.

[0125] (9) Uneven thickness of conductive layer

[0126] Regarding the uneven thickness of the conductive layer, the cross-section of the molded article was obtained by cutting at any 5 points in a direction perpendicular to the thickness of the molded article using a manual rotating microscope microtome (manufactured by Leica Microsystems Co., Ltd., "HistoCore BIOCUT" (registered trademark) R). The cross-section of the conductive layer was observed at 100,000 magnification with an accelerating voltage of 20 kV. The standard deviation of the measured values ​​was calculated and evaluated according to the following criteria.

[0127] A: A standard deviation of less than 1.5 is considered a good result.

[0128] B: The standard deviation is greater than 1.5 but less than 2.5, which is not a problem in practical use.

[0129] C: Standard deviation greater than 2.5, not practical.

[0130] (10) In-plane deviation of electromagnetic wave shielding effect

[0131] For any 5 locations of the molded article obtained by method (7), the KEC method (electric field) was used to measure the electromagnetic wave shielding effect (dB) at a frequency of 300MHz using a spectrum analyzer, and the measured values ​​were evaluated according to the following criteria.

[0132] A: A difference of less than 5 between the maximum and minimum values ​​is considered a good result.

[0133] B: The difference between the maximum and minimum values ​​is greater than 5 but less than 10, which is not a problem in practice.

[0134] C: The difference between the maximum and minimum values ​​is greater than 10, so it cannot be used practically.

[0135] The materials used are as follows.

[0136] (Organosilicon resin A)

[0137] Alkyd modified silicone resin (Shin-Etsu Chemical Industry Co., Ltd. X-62-900B).

[0138] (Organosilicon resin B)

[0139] Addition reaction type silicone resin (DOWSIL (registered trademark) LTC750A manufactured by Dow TORAY Co., Ltd.).

[0140] (Particle A)

[0141] Silver particles (manufactured by Fukuda Metal Foil Powder Industry Co., Ltd., AgG-204B, average particle size 1.8μm, kidney-shaped, aspect ratio 2.2).

[0142] (Particle B)

[0143] Silver particles (manufactured by Dowa Electronics Co., Ltd., AG-2-1C, average particle size 0.8μm, spherical, aspect ratio 1.0).

[0144] (Polyester Resin A)

[0145] Saturated copolyester resin (manufactured by UNITIKA Co., Ltd., "ELITEL" (registered trademark) XA-0847, glass transition temperature 58°C, weight-average molecular weight 8000, acid value 10mg / KOH).

[0146] (Polyester Resin B)

[0147] Polyurethane modified polyester resin (manufactured by Toyobo Co., Ltd., "BYRON" (registered trademark) UR-4800, glass transition temperature 106℃, weight average molecular weight 25000, acid value 4mg / KOH).

[0148] (Polyester Resin C)

[0149] Saturated copolyester resin (manufactured by UNITIKA Co., Ltd., "ELITEL" (registered trademark) UE-3320, glass transition temperature 38°C, weight-average molecular weight 1800, acid value 1 mg / KOH).

[0150] (Polyester Resin D)

[0151] Saturated copolyester resin (manufactured by Toyobo Co., Ltd., "BYRON" (registered trademark) GK-810, glass transition temperature 46℃, weight average molecular weight 6000, acid value 5mg / KOH).

[0152] (Polyester Resin E)

[0153] Saturated copolyester resin (manufactured by UNITIKA Corporation, "ELITEL" (registered trademark) KA-5034, glass transition temperature 67°C, weight-average molecular weight 9000, acid value 7 mg / KOH).

[0154] (Acrylic resins)

[0155] Acrylic resin (manufactured by Taisei Fine Chemicals Co., Ltd., 8DL-100, glass transition temperature 90°C, weight-average molecular weight 8000, acid value 1 mg / KOH).

[0156] (Injection Resin A)

[0157] Polybutylene terephthalate resin (Toray Industries, Inc. "TRECON" (registered trademark) 1101G).

[0158] (Injection Resin B)

[0159] Polyacrylonitrile-butadiene-styrene resin (Toray Industries, Inc. "TOYOLAC" (registered trademark) 100).

[0160] [Example 1]

[0161] <Preparation of Demolding Layered Film>

[0162] The materials of the release layer shown in Table 1 were dissolved in methyl ethyl ketone. The raw materials were mixed and dispersed using a homogenizer (manufactured by PRIMIX Co., Ltd.) to obtain a release layer coating composition with a solid content of 3.0% by mass. As the substrate film, a biaxially stretched polyethylene terephthalate film (manufactured by Toray Industries, Inc., "Lumirror" (registered trademark) S10) with a thickness of 38 μm was used. The above-mentioned release layer coating composition was coated by gravure printing coating method. After drying at 120°C, a release layer laminate film with a release layer thickness of 0.05 μm was obtained and wound into a roll.

[0163] <Preparation of Molding Film for In-Mold Transfer>

[0164] The raw materials used to obtain the conductive layer were configured as shown in Table 1. They were dispersed or dissolved in DMEA as an organic solvent and kneaded using a three-roll mill to obtain a resin mixture for the conductive layer. Next, the resin mixture and ethyl methyl ketone were mixed and dispersed using a homogenizer (manufactured by PRIMIX Co., Ltd.) to obtain a conductive layer coating composition with a solid content of 30.0% by mass. The conductive layer coating composition was applied to the release layer of the release film using gravure printing and dried at 120°C to form a 10 μm thick conductive layer. Then, an adhesive layer coating composition (vinyl chloride-vinyl acetate copolymer adhesive K588HP manufactured by Toyo Ink Co., Ltd.) was applied using gravure printing, dried, and cured to form a 10 μm thick adhesive layer, resulting in an in-mold transfer molding film, which was then wound into a roll.

[0165] <Production of Molded Products>

[0166] Molded articles were manufactured using the method described in "(7) Processing adaptability of molding process". The resulting conductive layer, resin, in-mold transfer molding film, and molded articles were evaluated for each evaluation item. The evaluation results are shown in Table 1.

[0167] [Examples 2-11, Comparative Examples 1-3]

[0168] Except that the release layer, particles, resin, injection resin, and adhesive layer are as described in Tables 1 and 2, the in-mold transfer molding film and molded article were prepared in the same manner as in Example 1. It should be noted that no release layer was provided in Comparative Example 1. The evaluation results of the in-mold transfer molding film and molded article are shown in Tables 1 and 2.

[0169] [Table 1]

[0170]

[0171] [Table 2]

[0172]

Claims

1. A molding film for in-mold transfer, comprising, in sequence, a substrate film, a release layer, and a conductive layer, wherein the thickness of the conductive layer is 5 μm or more and 15 μm or less, the conductive layer contains 60% or more and 91% or less particles in 100% by mass of the conductive layer, the conductive layer contains 9% or more and 40% or less polyester resin, the weight-average molecular weight of the polyester resin is 5000 or more and less than 10000, and for the conductive layer, a glass transition temperature is observed in the range of 40°C or more and 100°C when heated from 20°C to 250°C at a rate of 20°C / min under a nitrogen atmosphere using differential scanning calorimetry. The particles comprise one or more selected from carbon, silver, gold, copper, nickel, chromium, palladium, indium, aluminum, zinc, and platinum with a zero valence. The particles are a first particle with an aspect ratio of 1 or higher but less than 2, and a second particle with an aspect ratio of 2 or higher. The content of silicone resin in the release layer is 80% by mass or more.

2. The molding film for in-mold transfer according to claim 1, comprising, in sequence, the substrate film, the release layer, the conductive layer, and the adhesive layer.

3. The molding film for in-mold transfer according to claim 1, wherein, The silicone resin is an alkyd-modified silicone resin.

4. The molding film for in-mold transfer according to claim 1, wherein, The acid value of the polyester resin is above 5 mg KOH / g and below 20 mg KOH / g.

5. The molding film for in-mold transfer according to claim 1, wherein, The electromagnetic shielding effect of the in-mold transfer molding film was measured to be above 40dB using the KEC electric field method with an electromagnetic wave frequency of 300MHz.

6. The molding film for in-mold transfer according to claim 1, wherein, The substrate film is a polyethylene terephthalate film.

7. A method for manufacturing a molded article, comprising the steps of placing the in-mold transfer molding film of claim 1 in a mold, and then injecting molding resin and / or molding resin precursor.

Citation Information

Patent Citations

  • Molded film and its manufacturing method, and molded body and its manufacturing method

    JP2021192960A

  • Method of coating strip material

    US2681294A

  • Transfer film for in-mold molding and in-mold molded product having electromagnetic wave shielding properties

    JP2006297642A

  • Transfer foil for in-mold having embossed layer serving also as hard coat layer, method of manufacturing the same and injection molded article

    JP2012201016A